Benjamin Franklin and the American Revolution - Dull, Jonathan R., 1942- (University of Nebraska Press, 2010)
The inventor, the ladies' man, the affable diplomat, and the purveyor of pithy homespun wisdom: we all know the charming, resourceful Benjamin Franklin. What is less appreciated is the importance of Franklin's part in the American Revolution: except for Washington he was its most irreplaceable leader. Although aged and in ill health, Franklin served the cause with unsurpassed zeal and dedication. Jonathan R. Dull, whose decades of work on The Papers of Benjamin Franklin have given him rare insight into his subject, explains Franklin's role in the Revolution, what prepared him for that role, an.